Awareness, Significance, and Adoption of Sustainable ‎Agricultural Practices for Agricultural Productivity:‎Investigating The Case of The Indian Agricultural Sector - Jayaraj, Mr. Andrew; B, Dr. Harani (International Journal of Basic and Applied Sciences, 2025)
The present study focuses on examining awareness, importance, and adoption of Sustainable Agricultural Practices (SAPs) in the Indian ‎agricultural sector with reference to its impact on enhancing production and sustainability. The research investigates how government policies, education, and availability affect the decline of these practices among farmers, on the one hand, by identifying the very constraints that hamper their universal applicability. A mixed methods approach is used to combine results of quantitative survey ‎data from across India with qualitative insights from in-depth interviews with farmers and agricultural experts. The results show a ‎considerable disparity among the farmers in terms of knowledge and adoption of SAPs, which were more prevalent among farmers with better ‎education and accessibility. On the other hand few challenges include a lack of financial support, limited accessibility to clean and sustainable ‎technologies, and a reluctant attitude towards future benefits. Important gaps emerged in the execution of government policy, and change was ‎seen to have been stymied through inconsistent government support. Finally, the study recommends some suggestions for enhancing SAPs ‎and concludes with farmer education, improved access to more sustainable technologies, and increased policy implementations. These ‎recommendations, when implemented, can help the Indian agriculture sector become more productive, sustainable, and resilient, thereby ‎contributing towards the country’s long-term agricultural goals‎.